PENINGKATAN BUDAYA LITERASI BAGI MASYARAKAT MILENIA PEDESAAN - Juariyah Juariyah; Putri Robiatul Adawiyah (Universitas Muhammadiyah Jember, 2021)
This research focuses on the Study of Literacy Culture for Rural Millennial Communities in the knowledge of using simple application technology, YouTube and Google Content Censorship Filters. The Indonesian nation has a low literacy level, this is because the culture of reading and writing has not become part of the daily life of our society. YouTube is one of the most famous video sharing sites in the world. Availability of services on YouTube social media to access and obtain video data from YouTube. can be used in making website-based applications in the form of video content filters on YouTube, especially educational content aimed at learning. Jember Regency is one of the regencies in East Java which has people who still do not understand the ability to use technology intelligently and effectively. The danger will slowly emerge from the use of internet technology which is currently considered normal, in the future if there is no adult understanding, namely parents in rural millennial communities who are currently starting to be literate in information technology. As explained in the publication related to the welfare of the people of the Ajaember Regency in 2019 in the field of education, the Central Statistics Agency (BPS) noted that not all residents of Jember can experience or receive education. Therefore, it is important to have a smart awareness in literacy in society as a material and effort that balances the progress development of information technology